Rambu-rambu Penyusunan Skala Sikap Model Likert untuk Mengukur Sikap Siswa - Mawardi Mawardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
The general finding shows that the assessment instrument for attitude domain contained in each of the sub-theme in Buku Guru SD / MI, uses the rubric of student behavior observations, even though theoretically the nature of attitude is not the same as behavior, this shows the problem in the implementation of the Curriculum 2013. Ideally, the attitude domain assessment uses attitude measurement instruments, which include components of cognition, affection, and conation. Cognition is related to beliefs (beliefs, ideas, and concepts). The affection component concerns a person's emotional life, while the conation component is a tendency to behave. The three components of attitude do not stand alone, but interact with one another in a complex way. To overcome this problem, direction needs to be prepared for the correct attitude assessment instrument, especially containing the nature of attitudes and their differences with behavior, how to measure attitudes, and how to arrange the attitude scale of the Likert model. The steps in preparing the Likert model attitude scale include are: 1) compiling the attitude object statement; (2) conducting instrument trials; (3) determiinge the score for each statement (instrument blue-print); (4) analyzing items to determine the reliability and validity of the instrument.